PREDICTION OF DECREASE IN OVARIAN RESERVE IN ADOLESCENT GIRLS USING A COMPUTER PROGRAM - Светлана Ивановна Елгина; Елена Николаевна Никулина (The Publishing House Medicine and Enlightenment, 2020)
Aim - development of a computer program for assessing ovarian reserve in adolescent girls and forecasting its decline. Object of research. The object of the study were 200 adolescent girls 15-16 years old born premature and full-term. Materials and Methods. The purpose of the study is to develop a computer program to assess the ovarian reserve in adolescent girls and predict its decline, studied by laboratory, ultrasound, statistical methods. Results. Statistically significant differences of the main indicators characterizing the ovarian reserve in adolescent girls born prematurely compared to those born full-term were established. On the basis of the information obtained, a computer program was developed using the logistic regression method to identify markers that determine the prediction of ovarian reserve in adolescent girls, which was tested on an independent sample. The sensitivity of this method of predicting the risk of reducing the ovarian reserve was 70.9 %, and the specificity was 75.7 %. The computer program «forecasting of the risk of ovarian reserve decrease in teenage girls» is developed and registered (the certificate on the state registration of the computer program N 2019662373, date of the state registration in the register of computer programs - 23.09.2019. Federal service for intellectual property, Moscow). Conclusion. The ovarian reserve prediction program «predicting the risk of ovarian reserve decline in adolescent girls», based on the determination of laboratory and ultrasound markers, can be recommended for routine use to identify the risk group for ovarian reserve decline and a more differentiated approach to preventive measures.